Immediate coronary angiogram in out-of-hospital cardiac arrest patients with non-shockable initial rhythm and without ST-segment elevation — Is there a clinical benefit?. (October 2020) - Voicu, Sebastian; Bajoras, Vilhelmas; Gall, Emmanuel; Deye, Nicolas; Malissin, Isabelle; Dillinger, Jean-Guillaume; Benajiba, Chakib; Logeart, Damien; Henry, Patrick; Megarbane, Bruno; Sideris, Georgios
Abstract: Aim: Coronary angiogram (CA) may be useful after resuscitated out-of-hospital cardiac arrest (OHCA), but data regarding its benefit in patients with non-shockable initial rhythm without ST-segment elevation is scarce. We aimed to evaluate the prevalence of acute coronary syndrome (ACS) and survival in OHCA patients with non-shockable initial rhythm without ST-segment elevation and compare them to patients with shockable initial rhythm without ST-segment elevation. Methods: Retrospective single-centre study approved by the ethics committee of our institution, including adults successfully resuscitated from OHCA of presumed cardiac cause, undergoing routine CA on admission. Baseline characteristics, angiographic data including presence of ACS and survival were compared between patients with non-shockable and shockable initial rhythm focusing on patients without ST-segment elevation. Results: Among 517 patients included between 2002 and 2018, 311 had no ST-elevation, of whom 179 had non-shockable and 132 shockable initial rhythm. Compared with shockable initial rhythm patients without ST-elevation, non-shockable initial rhythm patients without ST-elevation had longer no-flow duration, 5 (1−10) versus 2 (0−8) min, p = 0.024, more frequent shock requiring vasopressors, 72% versus 47% p < 0.0001, a lower prevalence of ACS, 2 (1%), versus 29 (22%), p < 0.001 and higher mortality, 85% versus 39% (p < 0.0001). Among ACS patients, none survived in the non-shockable without ST-elevation group, while 20 (69%) survived in the shockable rhythm without ST-elevation group. Conclusions: Prevalence of ACS in patients without ST-segment elevation and non-shockable initial rhythm is extremely low, and survival extremely poor, therefore routine emergency CA does not seem beneficial in these patients.